SEKOLAH DASAR BERBASIS SENTRA DI KOTA PONTIANAK - Lyla Nursyahbani; Muhammad Nurhamsyah; Lestari Lestari (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
Children are the future successors of the nation, so their growth and development must be maximized, especially for children in the childhood phase. Therefore, it is hoped that all parties can support the creation of a good and child-friendly environment for their development. Indonesia has a target for all regions to become a Child Friendly City/ District (KLA) by 2030. One of the KLA indicators is Child Friendly Schools (SRA), which is manifested in the implementation of a child-friendly learning process. Schools must be able to use the right learning approach for optimal child development. One method that is considered appropriate for the child's development stage is the Beyond Centers and Circle Time (BCCT) method, which in Indonesia is known as senling or short for centers and circles. The BCCT method is a learning method that is applied based on certain areas and is centered on children as learners. This method aim is to develop all aspects of multiple intelligence in early childhood through directed play by moving classes. The purpose of this is to find out how to design a BCCT based primary school using design method by J.C. Jones. The concept of space is formulated by applying textures, colors, flexible spaces and individual spaces that can support children's development.